Искусство властвовать: перевод с китайского / авт. предисл., пер., коммент. З. Г. Лапина, Г. В. Зиновьев - Лапина З. Г. (Каноны, 2001)
Экземпляры: КХ (20030327) / Инвентарный номер: 1048045 / Цена: 107.53 / Сис.шифр: 87.3(3/8) / Авт.знак: И 86 / ГРНТИ: 02 / ББК: 87.3(5Кит)